Odontometric parameters as a forensic tool for stature estimation among three Asian ethnicities - Bharath Rao K; Madhumitha Natarajan; Arul Amalan; Runki Saran; Ravi Gupta; Saurabh Kumar; Amith Singh; P. Kalyana Chakravarthy (Egyptian Journal of Forensic Sciences, 2019)
Abstract Background The height of an individual in the upright posture is referred to as stature. The evaluation of the stature of an individual is an essential step in identification. Estimation of stature is commonly performed using the long bones as they positively correlate with the stature. The correlation between the dimensions of the skull, jaw and stature of an individual has been reported among specific populations. To date, only a few studies have correlated odontometric parameters with stature among populations. Teeth and oral structures can be used to estimate the stature of an individual. The objective of our study was to determine and establish a relationship to estimate the stature of individuals among three different Asian ethnicities using four odontometric parameters as a forensic tool. The Asian ethnicities chosen in our study were Malay, Indian and Chinese. The five parameters were the height of an individual, intercanine width, interpremolar width, arc length and mesiodistal dimension of the six anterior teeth. The height was measured with the individual standing upright and barefooted. The mesiodistal width of the anterior teeth was measured at the contact points; the intercanine and interpremolar widths were measured at the cusp tips from the left to the right quadrant; the arc length was measured at the middle one-third position of the crown from the right to the left canine. Results The results showed that out of the four odontometric parameters, only the arc length was significantly associated with the height of the individuals among the ethnicities chosen. Conclusion Thus, of the four selected parameters, the arc length may be helpful in the estimation of stature among the selected Asian ethnicities. Dimensions of the teeth can be used as an adjunct to other aids in estimating the stature of an individual and hence is a vital forensic tool.